PENGARUH RELIGIUSITAS DAN GENDER TERHADAP PENILAIAN ETIS (ETHICAL JUDGEMENT) MAHASISWA AKUNTANSI MINANGKABAU.” - Nadia Nila Henda Resty (Universitas Negeri Padang, 2018)
This study aims to empirically analyze the effects of religiosity and gender on ethical judgments (ethical judgment) of Minangkabau accounting students. This type of research is causative research. The population in this study were all accounting students in four Padang city colleges, Padang State University, Andalas University, Bung Hatta University, Putra Indonesia University (UPI YPTK) Padang. The sample was chosen as many as 898 respondents. The data used in the study are primary data derived from questionnaires distributed to respondents. This study uses multiple regression analysis with SPSS 21 software. The results showed that the variables of high religiosity (X1) and low religiosity (X2) had a significant positive effect on ethical assessment (Y). women are not more important in doing ethics (ethical judgment). The third hypothesis is rejected.Keywords: high religiosity, low religiosity, gender, ethical judgment